Terahertz Communication and Sensing Framework Based on Orthogonal Delay-Doppler Division Multiplexing Modulation - Meilin LI; Chong HAN (Leida xuebao, 2025)
Because the Terahertz (THz) band is capable of achieving terabit-per-second communication rates and high-precision sensing, THz Integrated Sensing And Communication (ISAC) has become a key technology for future wireless systems. We propose a THz ISAC framework based on a delay-Doppler waveform, i.e., the Orthogonal Delay-Doppler Multiplexing (ODDM) modulation. A more general off-grid ODDM modulation input/output relationship is derived to eliminate the assumption that channel path delays and Doppler frequency shifts are integer multiples of their resolutions. For ODDM symbol detection, a time-domain channel equalizer based on the conjugate gradient method is proposed to optimize the computational complexity. Compared with orthogonal frequency division multiplexing, ODDM demonstrates higher Doppler robustness against the Doppler effect. A sensing estimation algorithm is designed to achieve high-precision estimates with low complexity. The results show that the multi-target estimation accuracy approaches Cramér-Rao Lower Bounds (CRLB).